Economic Growth, Agriculture, Capital Formation and Greenhouse Gas Emissions in Indonesia: FMOLS, DOLS and CCR Applications - Hardi, Irsan; Idroes, Ghalieb Mutig; Zulham, Teuku; Suriani, Suriani; Saputra, Jumadil (Ekonomikalia Journal of Economics, 2023)
Economic growth drives increased demand for resources, placing greater pressure on the agricultural sector. While the adoption of advanced technologies and increased capital investment can enhance productivity, they also have environmental consequences, contributing to greenhouse gas emissions. Based on this interconnected issue, this study aims to examine the long-term relationships between economic growth, agricultural productivity, gross fixed capital formation, and greenhouse gas emissions in Indonesia, utilizing data from the period 1965-2021. The study employs the Dynamic Ordinary Least Squares (DOLS) and Fully-Modified Ordinary Least Squares (FMOLS) methods, and includes robustness checks using the Canonical Cointegration Regressions (CCR) method. To provide a more comprehensive insight, the study also employs the pairwise Granger causality approach to detect the direction of the relationships. In concise terms, the results suggest that agricultural productivity, gross fixed capital formation, and greenhouse gas emissions have a positive long-term influence on economic growth. Additionally, gross fixed capital formation has a negative effect, while economic growth has a positive long-term impact on agricultural productivity. Furthermore, agricultural productivity has a negative impact, while economic growth indicates a positive long-term effect on gross fixed capital formation. Moreover, economic growth positively influences greenhouse gas emissions over the long term. Lastly, the study found three bidirectional causalities, with greenhouse gas emissions as the central figure. These important findings provide crucial information for policymakers, economists, and environmentalists, giving a nuanced understanding of the intricate relationships between economic activities and environmental consequences, as well as aiding in the formulation of sustainable strategies for green economic growth, especially in Indonesia.